Academician Boris Vasilyevich Petrovsky (1908–2004) (on the 115th anniversary of his birth) - Al. A. Kurygin; V. V. Semenov (Вестник хирургии имени И.И. Грекова)
Outstanding Soviet surgeon, scientist, teacher, health care organizer and public figure, founder of the largest scien tific and practical school of surgeons, Minister of Health of the USSR (1965–1980), Hero of Socialist Labor (1968), academician of the USSR Academy of Medical Sciences (1966) and the USSR Academy of Medical Sciences (1957) (RAS and RAMS since 1991), laureate of the Lenin Prize (1960) and the State Prize of the USSR (1971), Honored Scientist of the RSFSR (1957), Professor Boris Vasilyevich Petrovsky was born on June 14 (27 according to the new style), 1908 in the CITy of Essentuki in the family of a doctor. In 1926, he entered the medical faculty of Moscow State University, in 1930, he received a medical diploma and worked as a surgeon in a regional hospital in the Moscow region, and in 1932, he was appointed to the position of the researcher at the Moscow Oncology Institute under the leadership of Professor P.A. Herzen. During the Soviet-Finnish and the Great Patriotic Wars, he served as a surgeon in various hospitals. In 1947, he defended his doctoral dissertation «Surgical treatment of gunshot wounds of blood vessels at the front line». In 1951, B. V. Petrovsky was elected the head of the department of faculty surgery of the pediatric faculty of the 2nd MMI named after N. I. Pirogov, and in 1956 – the head of the department of hospital surgery of the 1st MMI named after I. M. Sechenov. In 1963, the All-Union Scientific center for Surgery of the USSR Academy of Medical Sciences was created in Moscow, the organizer and director of which (1963–1988) was Boris Vasilievich (since 1989 – honorary director of the All-Union Scientific center for Surgery). At the same time, from 1965 to 1980, he headed the USSR Ministry of Health. Academician B. V. Petrovsky created the largest scientific and practical surgical school in the history of our country, which included more than 150 doctors of medical sciences. He was the author and co-author of about 700 scientific papers, including 45 monographs and manuals devoted to vari ous problems of cardiovascular, thoracic, abdominal, and military field surgery. Boris Vasilievich was the member of 34 international societies, associations, academies and colleges, as well as the honorary member of 14 foreign surgical societies. Academician B. V. Petrovsky died on May 4, 2004 and was buried at the Novodevichy cemetery in Moscow.